SYNTHESIS OF SILVER NANOPARTICLES USING BIOREDUCTOR OF KETAPANG LEAF EXTRACT (Terminalia catappa) AND ITS POTENTIAL AS SUNSCREEN - Payapo Irfa Apriliyanti; Muhammad Zakir; Nunuk Hariani Soekamto (Hasanuddin University, 2017)
Synthesis of silver nanoparticles is done by the chemical reduction method using the extract of leaves of catappa (Terminalia catappa) which acts as a reducing agent with the use of AgNO3 as the precursors. The results, based on changes in color, pH, and UV-Vis absorption shows color changes from yellow to yellow-brown with a pH of 4 indicating the formation of silver nanoparticles with a wavelength range from 412,50- 404,00 nm for the storage of the first day until the seventh day with a particle size 92,48 nm based on the results of taking the measurements of PSA. Analysis of functional groups that play a role in the synthesis using FT-IR. Characterization using XRD showed that the synthesized form a cubic crystal with a crystal size of 53,48 nm. Silver nanoparticles are used as a sunscreen with a blend of hydroxy cinnamic acid compounds. Testing activities determined sunscreen with SPF values were analyzed using a UV-Vis spectrophotometer. Results of testing the activity of sunscreen alloy nanoparticles of silver and hydroxy cinnamic acid (AHNP) with a concentration of 16 μg/mL - 20 μg/ml showed the consecutive SPF value 20,97; 24,71; 26,41; 28,07 and 31,92. Sunscreen AHNP activity increases with the concentration AHNP. Based on the research results can be concluded that the combination of ultra AHNP has a protective effect (SPF ≥ 15) against UV-B rays.